MORPHOLOGICAL CHANGES OF THE PROSTATE GLAND IN EXPERIMENTALLY SIMULATED PROSTATIC HYPERPLASIA AGAINST THE BACKGROUND OF ETHANOL INTOXICATION - Makodrai, Yu.I.; Klishch, I.M.; Nebesna, Z.M. (World of Medicine and Biology, 2023)
The scientific work is devoted to the study of the peculiarities of the prostate gland morphological changes in simulated benign hyperplasia under the influence of ethanol. The study was conducted on adult white male laboratory rats, weighing 190–250 g, divided into 2 groups. As a result of the study, it was established that during the toxic effect of ethanol on the 28th day of the experiment, venous stasis, destruction and spasm of the arterial bed, reorganization of acini, excretory ducts and components of connective tissue, growth of collagen fibers and periacinar, periductal and perivascular connective tissue fibrosis were present in prostate tissue under conditions of simulated hyperplasia. Lymphocytic infiltration was revealed, the hypertrophied secretory portions were lined mainly with columnar epithelial cells, the lumen was filled with large oxyphilic prostatic concretions. Excretory ducts were characterized by the expansion of lumens with the accumulation of secretions, atrophy of the epithelial layer, edema, and histoleukocyte infiltration. So, under the conditions of simulated alcohol intoxication, destructive and proliferative changes of the secretory departments, excretory ducts, remodeling of the connective tissue components of the prostate gland, which occur against the background of vascular disorders, were established.